2022
DOI: 10.3390/ijerph19053030
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Lifting Height and Load Mass for Muscular Workload during Supermarket Stocking: Cross-Sectional Field Study

Abstract: High physical work demands increase the risk of musculoskeletal disorders and sickness absence. Supermarket work involves a high amount of manual material handling. Identifying specific ergonomic risk factors is an important part of occupational health and safety efforts in the supermarket sector. In this cross-sectional field study among 64 supermarket workers, we used electromyography during the workday to determine the influence of lifting height and load mass on muscular workload of the low-back and neck/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(146 reference statements)
2
0
0
Order By: Relevance
“…Previous research manifested similar findings during a simulated drilling task [70] and among a convenience sample of supermarket workers [71,72]. Occupational lifting with arms above shoulder height resulted in higher muscular workload based on sEMG measurements and higher compression forces in the shoulder joints based on a musculoskeletal modelling approach [71,72]. The above mentioned findings elaborate on previous studies showing that elevated arm work increases the biomechanical load of the shoulder muscles and restricts the blood supply to shoulder and arm tissues [73].…”
Section: Construction Work and Biomechanical Loadsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous research manifested similar findings during a simulated drilling task [70] and among a convenience sample of supermarket workers [71,72]. Occupational lifting with arms above shoulder height resulted in higher muscular workload based on sEMG measurements and higher compression forces in the shoulder joints based on a musculoskeletal modelling approach [71,72]. The above mentioned findings elaborate on previous studies showing that elevated arm work increases the biomechanical load of the shoulder muscles and restricts the blood supply to shoulder and arm tissues [73].…”
Section: Construction Work and Biomechanical Loadsupporting
confidence: 78%
“…The present study showed an even distribution on the physical workload between the dominant and non-dominant side (Table 2) as well as an increased physical workload on the neck/shoulder muscles when the bricklayers performed their work above shoulder height. Previous research manifested similar findings during a simulated drilling task [70] and among a convenience sample of supermarket workers [71,72]. Occupational lifting with arms above shoulder height resulted in higher muscular workload based on sEMG measurements and higher compression forces in the shoulder joints based on a musculoskeletal modelling approach [71,72].…”
Section: Construction Work and Biomechanical Loadsupporting
confidence: 58%